SERVICIOS DE SALUD DE LOS ELITES SUCRE A LAS COMUNIDADES - Hallasi Roselló y Cols., Dilma Diany (2019)
The action of the brigades of health of the Traveling Local Equipment of Extramural Work in Health (ELITES) of the Ministry of Salud (MINSA) with support of the European Community, in benefit of the Peruvians from excluded zones, is little well-known. This service goes back to 1905. As of June of 1998 it was settled down like constant attention. The population of the communities when they became ill did not receive any type of attention, now are taken care of in medicine, odontology, nursing and obstetrics mainly. ELITES supports in the promotion and joint of the services organizing with the authorities of the communities in the formation of the Committees of Communal Development (CODECO). Also, it organizes and enables the health promoters. The members of the equipment arrive at the communities on foot carrying in their knapsacks the basic equipment, medicines and their personal effects. They share the food of the population and sleep in the atmospheres that they provide to them. The brigades are good image for the government in the aspect health.